Ethnic boundaries and boundary-making in handicrafts: examples from northern Norway, Sweden and Finland - Schilar, Hannelene; Keskitalo, E. Carina H. (Acta Borealia, 2018)
When ethnicity is said to be manifest and practised through handicrafts, these seemingly innocent objects become political. They raise questions concerning who can do what handicraft, who can use what symbols or what developments are “allowed”. They illustrate the continuous production of ethnic norms and boundaries, especially when global tourism enters into the equation. Taking a social constructivist perspective, our study addresses ethnic boundaries and boundary-making in handicrafts in northern Sweden, Norway and Finland. Our findings are based on fieldwork (35 interviewees) with people of diverse local backgrounds making and selling handicrafts. Methodologically, we avoid preselecting people based on ethnicity, but instead contribute to an understanding of the constitutive processes of ethnicity by looking at how ethnic talk comes into conversations about handicrafts. Our findings demonstrate that the interviewees draw an ethnic divide between “Sámi”/“non-Sámi”, while other ethnic-choices move to the background. This divide can be seen to be amplified by tourism. The boundary for who can make a Sámi handicraft or use Sámi symbols remains significant, yet also fluid. The article deepens the understanding of the Sámi/non-Sámi ethnic categorization, here in relation to handicrafts. It also helps unravel the complexities between tourism, ethnicities and handicrafts more broadly.